Factors Related to Water Filter Use for Drinking Tap Water at Home and Its Association With Consuming Plain Water and Sugar-Sweetened Beverages Among U.S. Adults. Issue 5 (June 2022) - Park, Sohyun; Onufrak, Stephen J.; Cradock, Angie L.; Hecht, Christina; Patel, Anisha; Chevinsky, Jennifer R.; Blanck, Heidi M.
Objective: To examine factors associated with water filter use (WFU) for drinking tap water at home and its association with consuming plain water and sugar-sweetened beverages (SSBs). Design: Quantitative, cross-sectional study. Setting: The 2018 SummerStyles survey data. Subjects: U.S. adults (≥18 years; N=4042). Measures: Outcomes were intake of plain water (tap/bottled water) and SSBs. Exposure was WFU (yes, no, not drinking tap water at home). Covariates included sociodemographics, weight status, Census regions, and home ownership status. Analysis: We used multivariable logistic regressions to estimate adjusted odds ratios (AOR) and 95% confidence interval (CI) for consuming tap water, bottled water, or total plain water >3 cups/day (vs. ≤3 cups) and SSBs ≥1 time/day (vs. <1 time) by WFU. Results: Overall, 36% of adults reported using a filter for drinking tap water at home; 14% did not drink tap water at home. Hispanics had significantly higher odds of using a water filter (AOR=1.50, 95% CI=1.14-1.98) vs non-Hispanic White. Factors significantly associated with lower odds of WFU were lower education (AOR=.69, 95% CI=.55-.86 for ≤high school; AOR=.78, 95% CI=.64-.95 for some college, vs college graduate), not being married (AOR=.81, 95% CI=.66-.98, vs married/domestic partnership), and lower household income (AOR=.68, 95% CI=.68-.90 for <$35, 000, vs ≥$100, 000). Using a water filter was associated with higher odds of drinking >3 cups/day of tap water (AOR=1.33, 95% CI=1.13-1.56) and lower odds of SSBs ≥1 time/day (AOR=.76, 95% CI=.62-.92). Not drinking tap water at home was associated with higher odds of drinking >3 cups/day bottled water (AOR=3.46, 95% CI=2.70-4.44). Conclusions: WFU was associated with higher tap water intake and lower SSB intake among U.S. adults. WFU was higher among Hispanics, but lower among those with lower education and income and not married adults. Although WFU was associated with healthful beverage habits, additional considerations for WFU may include source water quality, oral health, cost, and proper use.